Burnout, Compassion Fatigue and Vicarious Traumatic Experiences Among Social Workers: Emotional Regulation as a Protective Factor - Azam, Hooria; Rehman, Momina; Rehman, Misbah (Pakistan Journal of Humanities and Social Sciences, 2023)
This study was based on burnout, compassion fatigue and vicarious traumatic experience among social worker, and emotional regulation as a protective factor. The social workers were those who supported flood victims in different cities of Pakistan. The purpose of this study was to find the importance of emotional regulation among social workers in situations of burnout and compassion fatigue. Research participants were 200 individuals, with age range of 18 to 30 years (early adulthood). The data was collected from social welfare organizations. The study was quantitative in nature. Snowball sampling technique was used. The Emotional Regulation Questionnaire (ERQ) by Gross and John (Gross & John, 2003). Burnout, Compassion Fatigue and Vicarious Trauma Assessment by the Crisis & Trauma Resource Institute, were administered on the participants. To test the hypothesis regression analysis was used to determine the impact of emotional regulation on burnout, compassion fatigue and vicarious traumatic experience. Pearson Bivariate correlation analysis was used to determine the association between emotional regulation, vicarious trauma, compassion fatigue and burnout. Independent sample T Test was used to evaluate the gender differences in level of emotional regulation, burnout, compassion fatigue and vicarious traumatic experience. The result showed significant impact of emotional regulation on burnout, compassion fatigue and vicarious traumatic experience among social workers. The result also shows that there is significant negative correlation between burnout, compassion fatigue and vicarious traumatic experience. Hypothetical and actual results are closely related.